IMPLEMENTASI PATEN (PELAYANAN ADMINISTRASI TERPADU KECAMATAN) DALAM PENYEDERHANAAN BIROKRASI PERIZINAN - Kusumaningsih, Rila (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Public services with good service standards are one of the government's strategies to interact directly with the community. One of the public services is the Integrated Sub-district Administration Service (PATEN) where the public service delivery system is in the same location in a sub-district that also has a permit for its public service. The research method used is the normative legal research method or legal research method based on literature studies, focusing on the study of written legal sources such as laws, government regulations and related legal documents. Legal materials are from primary, secondary, and tertiary materials including laws and regulations, scientific journals, books, and legal guides and use the relevant statutory and regulatory approaches. Public service activities carried out by individuals or organizations in the form of goods and services to the community give rise to permits in the form of implementing laws and regulations. The PATEN policy originates from the center and is designed to be implemented uniformly throughout Indonesia and facilitates community involvement. The implementation of Integrated Sub-district Administrative Services is a strategic step in improving the quality of public services in Indonesia, with an emphasis on the principles of transparency, accountability, efficiency, and community participation. PATEN is designed to simplify the administration and licensing process, so that the public can access services more easily and quickly. PATEN is expected to support good governance and meet community expectations for public services.